Corporate values: A linguistic approach. (December 2015) - Bjørge, Anne Kari; Whittaker, Sunniva
Major corporations may as part of their communication strategy present a number of core values in the form of abstract property nouns, for example, integrity . Such nouns are rich in meaning, which gives rise to a corporate discourse associated with their interpretation. Multinational companies tend to use English as a lingua franca (ELF) to formulate these values in order to reach a global workforce, which in some cases may lead to a need for explicitation as a translation strategy to capture any cultural differences. To our knowledge, there is little prior in-depth research on corporate values, taking into account the linguistic material used, nor research into the linguistic expressions designating these as instances of discourse in their own right. The same applies to research into the implications of conveying these expressions by using ELF. On this background, we discuss corporate values from a linguistic perspective, adopting a semantic–pragmatic approach, including cultural factors and the implications of using ELF to convey their meaning. To illustrate our approach, we will present a case study of a Norwegian MNC with subsidiaries in 12 different countries.